Arabidopsis thaliana Ei-5: Minor Vein Architecture Adjustment Compensates for Low Vein Density in Support of Photosynthesis - Stewart, Jared J.; Polutchko, Stephanie K.; Demmig-Adams, Barbara; Adams, William W. (Frontiers in Plant Science, 2018)
An Arabidopsis thaliana accession with naturally low vein density, Eifel-5 (Ei-5), was compared to Columbia-0 (Col-0) with respect to rosette growth, foliar vein architecture, photosynthesis, and transpiration. In addition to having to a lower vein density, Ei-5 grew more slowly, with significantly lower rates of rosette expansion, but had similar capacities for photosynthetic oxygen evolution on a leaf area basis compared to Col-0. The individual foliar minor veins were larger in Ei-5, with a greater number of vascular cells per vein, compared to Col-0. This compensation for low vein density resulted in similar values for the product of vein density x phloem cell number per minor vein in Ei-5 and Col-0, which suggests a similar capacity for foliar sugar export to support similar photosynthetic capacities per unit leaf area. In contrast, the product of vein density x xylem cell number per minor vein was significantly greater in Ei-5 compared to Col-0, and was associated not only with a higher ratio of water-transporting tracheary elements versus sugar-transporting sieve elements but also significantly higher foliar transpiration rates per leaf area in Ei-5. In contrast, previous studies in other systems had reported higher ratios of tracheary to sieve elements and higher transpiration rate to be associated with higher – rather than lower – vein densities. The Ei-5 accession thus further underscores the plasticity of the foliar vasculature by illustrating an example where a higher ratio of tracheary to sieve elements is associated with a lower vein density. Establishment of the Ei-5 accession, with a low vein density but an apparent overcapacity for water flux through the foliar xylem network, may have been facilitated by a higher level of precipitation in its habitat of origin compared to that of the Col-0 accession.